AN EXPERIENCE OF CHORIONIC VILLUS SAMPLING IN LADY READING HOSPITAL, PESHAWAR - Syed, Wajeeha; Hayat, Nazish; Liaqat, Nazia; Rafiq, Sonia (Journal of Postgraduate Medical Institute, 2021)
Objective: To determine the outcome of chorionic villus sampling for prenatal diagnosis of inherited diseases. Methodology: This descriptive study was conducted on 70 antenatal ladies having 11 to 14 weeks singleton pregnancy and with history of genetic disorders in family or children. It was carried in the Department of Obstetrics and Gynaecology, Lady Reading Hospital, Peshawar. Chorionic villus sampling (CVS) was performed by Obstetrics and Gynae consultants via transabdominal route under local anaesthesia and ultrasound guidance. Written informed consent was taken from all the participating couples before starting the process. By using SPSS version 23, statistical analysis was done. Results: A total of 70 samplings were done. Miscarriage as a result of the procedure occurred in 1/70 (1.42%), significant pain requiring intramuscular analgesia occurred in 40 (57%) patients and there were no reported cases of infection. Failure to retrieve sample occurred in 4 (5.7%) patients requiring repeat procedure after 10 days. 3 (4.2%) patients reported vaginal bleeding within a week after the procedure. After DNA analysis of the submitted samples, it showed thalassemia major 15 (21.42%), thalassemia minor 30 (42.85%), no mutation 22 (31.42%) and down syndrome 1 (1.42%). Conclusion: Chorionic villus sampling was found to be a safe procedure for prenatal diagnosis of genetic disorders in first trimester.